Burnout and its Relationship with the Nurses' Characteristics - F Rafii; Shamsikhani S; Zarei M; Haghani M; Shamsikhani S (Iran University of Medical Sciences, 2012)
Background & Aims : A number of studies have been done on the topic of nurses' burnout. However social and cultural context of caring institutes and the characteristics of nurses working in these centers would add to the knowledge about this organizational behavior. Accordingly this study aims at identifying the frequency and intensity of nurses' burnout and its relationship with nurses' characteristics in hospitals affiliated to Arak University of Medical Sciences.   Material & Methods: It was a descriptive correlational study. Two hundred nurses working in hospitals affiliated to Arak University of Medical Sciences were recruited by Stratified probability sampling with proportional allocation. The instruments included Demographic information questionnaire and the Maslach Burnout Inventory (MBI). Data were analyzed by descriptive statistics, independent t- test, chi-square , and ANOVA using SPSS-PC (v. 16).   Result : The findings revealed that 39.5% and 37% of nurses have reported high levels of frequency and low levels of severity of emotional exhaustion respectively. The majority of nurses (75%) reported high levels of personal accomplishment frequency and 70% of them reported high levels of personal accomplishment severity. Nurses also reported low levels of frequency (47%) and intensity (45%) of depersonalization. Significant relationship was found between frequency of emotional exhaustion and sex (p=0.05), severity of emotional exhaustion and sex (p=0/05), and severity of depersonalization and age (P =0/04).   Conclusions: Identification of work place stressors in order to prevent emotional exhaustion, and also providing conditions for continuous job promotion and experiencing personal success for nurses working in Arak city is recommended.  Received: 15 Sep 2012   Accepted: 13 Nov 2012